2020
DOI: 10.2106/jbjs.20.01103
|View full text |Cite|
|
Sign up to set email alerts
|

A Reevaluation of the Risk of Infection Based on Time to Debridement in Open Fractures

Abstract: Update This article was updated on February 9, 2021, because of a previous error. On page 269, in the Note at the end of the article, the surname that had read “Merner” now reads “Mener.” An erratum has been published: J Bone Joint Surg Am. 2021 Mar 17;103(6):e25. Background: Open fractures are one of the leading causes of disability worldwide. The threshold time to debridement that reduces the infection rate is unclear. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 110 publications
0
26
0
Order By: Relevance
“…The BOA/BAPRAS standards replaced this threshold by advising on immediate debridement for grossly contaminated wounds or suspected compartment syndrome, debridement within 12 hours for solitary high-energy open fractures and debridement within 24 hours for all other low-energy open fractures [ 6 ]. A study of 77 open fractures by Patzakis et al and another meta-analysis involving over 18,000 patients by Goliath investigators showed increased risk of infection after 12 hours [ 16 , 17 ]. However, Hendrickson et al, in their retrospective review of 116 GA grade IIIB open fractures, showed no difference in infection rates when debridement is done before or after the 12-hour threshold [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BOA/BAPRAS standards replaced this threshold by advising on immediate debridement for grossly contaminated wounds or suspected compartment syndrome, debridement within 12 hours for solitary high-energy open fractures and debridement within 24 hours for all other low-energy open fractures [ 6 ]. A study of 77 open fractures by Patzakis et al and another meta-analysis involving over 18,000 patients by Goliath investigators showed increased risk of infection after 12 hours [ 16 , 17 ]. However, Hendrickson et al, in their retrospective review of 116 GA grade IIIB open fractures, showed no difference in infection rates when debridement is done before or after the 12-hour threshold [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed one-to-one propensity score-matched analysis for the administration of broad-spectrum antibiotics. We selected patient demographic characteristics and other potential confounding variables derived from previous studies 8 , 21 23 . Those factors included age, sex, body mass index (BMI), American Society of Anesthesiologists (ASA) class, smoking, diabetes mellitus, time to completion of debridement, open fracture location (i.e., upper vs. lower extremity), Gustilo–Anderson classification, and summative score of the OTA-OFC.…”
Section: Methodsmentioning
confidence: 99%
“…(2) “All open fractures were treated as emergencies,” whereas today many open fractures are operated in a timely basis but not necessarily as an emergency. As noted in the GOLIATH meta-analysis, 6 current recommendations suggest that open fractures should be surgically addressed within 12 hours, especially type III fractures.…”
Section: First Studymentioning
confidence: 99%
“…4,5 (2) “All open fractures were treated as emergencies,” whereas today many open fractures are operated in a timely basis but not necessarily as an emergency. As noted in the GOLIATH meta-analysis, 6 current recommendations suggest that open fractures should be surgically addressed within 12 hours, especially type III fractures.(3) The authors routinely cultured the wounds on admission and again before wound closure. Open fracture wounds are rarely cultured today unless the wound seems infected (not just contaminated).…”
Section: First Studymentioning
confidence: 99%